Using emissions trading schemes to reduce heterogeneous distortionary taxes: The case of recycling carbon auction revenues to support renewable energy - Claire Gavard; Sebastian Voigt; Aurélien Genty (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
While emissions trading schemes are developed by nations to mitigate their greenhouse gas emissions, behavioural studies have shown that the political and public acceptability of these market-based instruments depends on the way the associated revenues are used. One option the general public approves of is to use them to support renewable energy. If this consists in reducing a pre-existing electricity levy that heterogeneously applies to the various sectors of the economy, the reduction of this distortionary tax thanks to the carbon revenues results in general equilibrium effects that may have unequal sectoral impacts. This is what we examine in the case of the European Union. With a modelling approach including a detailed disaggregation of European sectors, we find that using auction revenues from the Emissions Trading Scheme (ETS) to support electricity generation from renewable sources results in a 2% rise in electricity demand in the whole economy due to the reduced electricity levy that electricity consumers have to pay to support renewable energy. This results in a 1.8% ETS carbon price increase. The carbon constraint for the non-ETS sectors is 5.9% looser as a consequence of the larger electricity use by these sectors. While the energy intensive sectors generally benefit from electricity levy exemptions, we observe that, due to the energy and ETS price increase, the combination of these exemptions and of the use of carbon auction revenues to support renewable energy makes the ETS sectors worse off than if carbon revenues are transferred to households. In aggregate, the recycling option analysed here results in a GDP gain due to its impacts on the non-ETS sectors, the reduction of the electricity levy and associated distortionary effects.
Keywords: C68; E62; H21; H23; Q42; Q54; 330; carbon auctions; renewable energy support; electricity levy; emissions trading scheme; revenues recycling